2013
DOI: 10.1021/ja401589a
|View full text |Cite
|
Sign up to set email alerts
|

Salt-Free Reducing Reagent of Bis(trimethylsilyl)cyclohexadiene Mediates Multielectron Reduction of Chloride Complexes of W(VI) and W(IV)

Abstract: We developed a salt-free reduction of WCl6 using 1-methyl-3,6-bis(trimethylsilyl)-1,4-cyclohexadiene (MBTCD) in toluene to give a low-valent trinulcear tungsten complex involving W(II) and W(III) centers, while in the presence of redox active ligands such as α-diketone and α-diimine the same reduction produced W(IV) complexes with the corresponding redox-active ligands, (α-diketone)WCl4 and (α-diimine)WCl4. A W(VI) complex with two α-diketone ligands, (α-diketone)2WCl2, was found to be synthetically equivalent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 73 publications
0
41
0
Order By: Relevance
“…The trimerization of ethylene may be carried out with the aid of a low‐valent tantalum catalyst generated by reduction of TaCl 5 with BTCD (Scheme ) 37a. Recently, they reported that this compound can be used as a 4e – reducing agent [W VI →W II ] 37b…”
Section: Low‐valent Nbiii In Catalytic Reactionsmentioning
confidence: 99%
“…The trimerization of ethylene may be carried out with the aid of a low‐valent tantalum catalyst generated by reduction of TaCl 5 with BTCD (Scheme ) 37a. Recently, they reported that this compound can be used as a 4e – reducing agent [W VI →W II ] 37b…”
Section: Low‐valent Nbiii In Catalytic Reactionsmentioning
confidence: 99%
“…These reagents have the stoichiometry to transfer two silyl groups in the same way that 1,4‐cyclohexadiene or dihydroanthracene supply two H. However, this transfer is not found in seemingly simpler silyl sources, R 3 Si‐SiR 3 because analogous to H 2 these disilanes lacks polarity. The utility of bis‐silyl pyrazines especially 1,4‐bis(trimethylsilyl)‐1,4‐diaza‐2,5‐cyclohexadiene, 1 , and the tetramethylated analogue, 2 (Scheme ) to abstract chloride and oxide from metal complexes have been actively explored, and this process clearly represents reduction of the metal center. We are interested in broadening the application of their reductive character, including to main group elements in the form of reductive silylation or deoxygenation, but also in the mechanism, concerted or stepwise, of these silyl transfer reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Mashima and Tsurugi have shown that 1 reduces binary W and Ti chlorides to lower oxidation states by chloride abstraction, a conversion which is perhaps even superior to using elemental Zn or Mg toward the same end. While it was originally envisioned that elimination of (Me 3 Si) 2 O from MO n by 1 might be a useful approach to MO n −1 , a recent application to support‐bound WO 3 gave instead tetravalent tungsten silyl esters, which is still a valuable 2 electron reduction, but without full elimination of W/O bonds and creation of lower metal coordination number .…”
Section: Introductionmentioning
confidence: 99%
“…Without the appropriate ligands, reductant‐derived salt (or its anion)‐contacted clusters typically form . We found that four‐electron reduction of WCl 6 proceeded upon the use of an excess amount of 1 b in toluene at room temperature to give low‐valent tungsten species in a salt‐free manner, and subsequent extraction with THF afforded a trinuclear tungsten cluster, W 3 Cl 7 (thf) 3 ( 11 ), having two divalent and one trivalent tungsten centers (Scheme ) . The molecular structure of complex 11 revealed that three tungsten atoms and three μ‐Cl ligands are arranged in an equilateral triangle and one μ 3 ‐Cl ligand is located above the triangle plane.…”
Section: Generation Of Reactive Low‐valent Group 6 Metal Speciesmentioning
confidence: 99%
“…[8] We herein highlight ac onceptually new approachf or "saltfree reduction for generatingc atalytically active low-valent metal species" by using organosiliconc ompounds of trimethylsilyl-substituted cyclohexadienes 1a and 1b,d ihydropyrazines 2a-c,a nd 4,4'-bipyridinylidene 3 as versatile reductants (Figure 1). [9] Upon reaction with metal complexes,o rganosili-con reductants 1-3 were converted into the corresponding aromatic compounds and two trimethylsilyl cations through two-electron redox events, as exemplified by 1a schematically shown in Figure 2. This salt-free reduction provides the ideal opportunity to observe any catalytic intermediates, because reductant-derived metal-salt contamination can be exclusively avoided.…”
Section: Introductionmentioning
confidence: 99%